Environmental Perception in rural communities surrounding a ReservePrivate Natural Heritage - Dias, Ozanan Almeida; Mota, Neidson Dias (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
Conservation Units(CU´s) are protected areasrecognized asimportant mean forprotecting nature. However, often theseresultsare not beingachievedmaking it necessary tostudy Environmental Perceptionin order to find out meaningsand attitudesof man withthe natural elementsand theUC's. This study aimed toanalyze theEnvironmental Perception of a rural communitysurrounding thePrivate Reserve ofNatural Heritage(PRNP), located inIúnaandMunizFreire villages -ES. Among the techniquesfor diagnosingEnvironmental Perception, it was applied a structured questionnairewithdiscursiveand objectivequestions. It was found thatthe preservationof water resourcesand wildlifeisthe primary concernof respondents, andthat humansperceivethe environmentaccording totheir needsand theuse they makeof it, identifying benefits ofpreservation and conservationof natureconcerning realityinwhich it is inserted.